The Economic Landscape of Digital Health: How Much Do AI Wearables Cost? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into wearable technology has ushered in a new era of personalized health monitoring and digital assistance. AI ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Wearable Technology; Healthcare Data